Normative data stratified by age and education for a Spanish neuropsychological test battery: Results from the Colombian Alzheimer's prevention initiative registry. Issue 2 (4th March 2021) - Torres, Valeria L.; Vila-Castelar, Clara; Bocanegra, Yamile; Baena, Ana; Guzmán-Vélez, Edmarie; Aguirre-Acevedo, Daniel C.; Tirado, Victoria; Munoz, Claudia; Henao, Eliana; Moreno, Sonia; Giraldo, Margarita; Acosta, Natalia; et al.
Abstract: Neuropsychologists continue to face challenges when assessing Spanish-speaking individuals due to limited availability of normative data. We developed comprehensive normative data stratified by age and education for a Spanish neuropsychological test battery used by the Grupo de Neurociencias de Antioquia (Colombia) and the Colombian Alzheimer's Prevention Initiative Registry, which have followed large families at risk for autosomal-dominant Alzheimer's disease (ADAD) since the 1990s. Approximately 75% of these individuals are cognitively-unimpaired and are not genetically predisposed to develop ADAD. We conducted a retrospective study on neuropsychological evaluations from 2, 673 cognitively unimpaired individuals (56% female), with ages ranging from 18 to 86 years and education from 1 to 25 years. Neuropsychological measures included the Consortium to Establish a Registry for Alzheimer's Disease-Colombia, and other multidomain Spanish tests. We examined associations between age, education, and sex with cognitive performance. Norms stratified by age and education are presented. Cognitive performance showed small associations with age and education and was unrelated to sex. We provided population-based norms for Spanish tests targeting multiple cognitive domains using a large Colombian sample. These normative data may be helpful for the neuropsychological characterization of Spanish speakers from Latin America in clinical and research settings.